Removal of Eggs Adhesiveness of African catfish (Clarias gariepinus) at Different Concentrations of Urea Solution - Amirul Asraf; Zainal A. Muchlisin; Mohd N. Siti-Azizah (Graduate Program of Syiah Kuala University, 2013)
Abstract –The objective of the present study was to determine the best concentration of urea solution and rinsing time to remove adhesiveness of African catfish eggs. Four different concentrations of rinse solution were used in this experiment comprising of 2 g, 4 g, 6 g and 8 g of urea diluted in 4 g NaCl/L of water producing a concentration of 0.486 mM, 0.973 mM, 1.458 mM, and 1.946 mM of urea concentration respectively, while 4 g NaCl/L of water without urea were used as control. The fish eggs were rinsed with the solutions at different durations namely; 1, 5 and 10 minutes. Each rinsing solution concentration and rinsing time were conducted in three replicates. The fertilization and hatching rates increased and peaked from the control (0 mM of urea) to 0.466 mN urea and decreased when concentration of urea was increased to 0.973 mM urea and 1.458 mM urea, then increased again at 1.946 mM urea, but these values were lower than at 0.486 mM urea. Thus, the best concentration for fertilization and hatching rates were 0.486 urea of urea. However 0.973 mM of urea was optimum in reducing clumping of eggs. Keywords: Clumping; Fertilization; Hatching; Brood fish